2004
DOI: 10.1021/es0492642
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Reflectance Spectroscopy for the Assessment of Soil Mercury Contamination

Abstract: Conventional methods for investigating soil Hg contamination based on raster sampling and chemical analysis are time-consuming and relatively expensive. The objective of this study was to develop a rapid method for investigating Hg concentration in suburban agricultural soils of the Nanjing region using reflectance spectra within the visible-near-infrared (VNIR) region. Several spectral pretreatments (absorbance, Kubelka-Munk transformations and their derivatives) were applied to the reflectance spectra to opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 19 publications
(20 reference statements)
1
68
2
Order By: Relevance
“…The monitoring of affected vegetation uses various methods such as sampling and chemical analysis of the soil, water, air and plants (Manzo et al, 2013;Nascimbene et al, 2014). However, these ground-based methods are time-consuming and expensive, especially when they are applied to large areas (Wu et al, 2005;Yi et al, 2007;Fauzi et al, 2013). Airborne or spaceborne remote sensing can simultaneously monitor relatively large areas quickly in a non-destructive fashion and could be integrated with a field-based approach, improving monitoring ability (Ayanu et al, 2012;Hunter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of affected vegetation uses various methods such as sampling and chemical analysis of the soil, water, air and plants (Manzo et al, 2013;Nascimbene et al, 2014). However, these ground-based methods are time-consuming and expensive, especially when they are applied to large areas (Wu et al, 2005;Yi et al, 2007;Fauzi et al, 2013). Airborne or spaceborne remote sensing can simultaneously monitor relatively large areas quickly in a non-destructive fashion and could be integrated with a field-based approach, improving monitoring ability (Ayanu et al, 2012;Hunter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the absorption features associated with electronic transitions of Fe 3+ and Fe 2+ ions in Fe-bearing minerals can be found in the near-infrared region at 780-1200 nm [33][34][35]. In addition, the absorption features of metals associated with molecular vibrations of organic and inorganic functional groups in organic matter, silicates, carbonates, and water can be found in near infrared at 780-2500 nm region [24,33,34,36].…”
Section: Application Of Near-infrared Spectroscopy (Nirs) For Analysimentioning
confidence: 99%
“…Wu et al [24,36] reported the feasibility of using NIRS for monitoring and predicting trace metals in suspended solids, sediment, and soil. This was achieved by quantitative evaluations of the spectral activity of sediment and soil properties [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Application Of Near-infrared Spectroscopy (Nirs) For Analysimentioning
confidence: 99%
See 2 more Smart Citations